2010
DOI: 10.1097/qai.0b013e3181caea89
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Detectable HIV-1 RNA at Delivery Among Women Receiving Highly Active Antiretroviral Therapy in the Women and Infants Transmission Study

Abstract: Background-Detectable HIV-1 RNA at delivery is the strongest predictor of mother-to-child transmission. The risk factors for detectable HIV, including type of regimen, are unknown. We evaluated factors, including highly active antiretroviral (HAART) regimen, associated with detectable HIV-1 RNA at delivery in the Women and Infants Transmission Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 20 publications
5
26
2
Order By: Relevance
“…While this percentage of women with persistent viremia at delivery is concerning, this estimate is lower than the 24% of HAART-naive women with detectable VL at delivery observed in an earlier U.S. cohort (18). The timing of HAART initiation, along with consistent usage during pregnancy, were associated with VL at delivery.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…While this percentage of women with persistent viremia at delivery is concerning, this estimate is lower than the 24% of HAART-naive women with detectable VL at delivery observed in an earlier U.S. cohort (18). The timing of HAART initiation, along with consistent usage during pregnancy, were associated with VL at delivery.…”
Section: Discussioncontrasting
confidence: 54%
“…While one previous report showed virologic response to vary by regimen type (17), a large observational study found no difference in response by ARV regimen (18). A randomized trial of women with CD4+ ≥200 cells/μL in Botswana comparing the impact of a nucleoside reverse-transcriptase inhibitor [NRTI]-based regimen to a boosted protease-inhibitor [PI]-based regimen on VL at delivery observed high rates of virologic suppression at delivery and no difference between regimens (19).…”
Section: Introductionmentioning
confidence: 92%
“…Of these, only one delivered vaginally. Employing the current BHIVA guidance could signifi cantly reduce the number of women having CS due to isolated low-level detectable viraemia and hence improved measures for virological control is essential (Katz et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of substance use in this population have historically been high; in the late 1980s and early 1990s, half of HIV-infected pregnant women used illicit substances [3, 4]. Substance use during pregnancy in HIV-infected women has negative implications for transmission [58], infant outcomes [919], and the health of the mother [20]. …”
Section: Introductionmentioning
confidence: 99%